Cephalometric changes in pharyngeal airway dimensions after functional treatment with twin block versus myobrace appliances in developing skeletal class II patients: a randomized clinical trial - Ahmed M. Madian; Dina Elfouly (BMC, 2023)
Abstract Background Several appliances have been used for correction of developing skeletal Class II, including different myofunctional appliances as Twin block (TB)as well as the new pre-fabricated Myobrace (MB) appliance. However, the effects of these devices on the pharyngeal airways have not been compared in the literature. Thus, the aim of this study was to compare the effects of two Class II correction appliances; TB and MB on the sagittal pharyngeal airway dimension (SPAD), including the nasopharyngeal airway area (NPAA), the oropharyngeal airway area (OPAA), and the laryngopharyngeal airway area (LPAA). Methods This is a two parallel arms randomized comparative clinical trial. Twenty-six children of 9-12 years with Skeletal Class II malocclusion due to mandibular deficiency and normal maxillary growth as confirmed by lateral cephalometric X-ray readings (ANB angle > 4° and SNB angle < 78) and Cervical vertebral maturational index (CVMI) 1 or 2 were randomly assigned into two equal groups. Group I: TB, Group II: MB (prefabricated functional appliance, Myofunctional Research Co., Australia). Lateral cephalograms were taken for all patients in both groups before treatment (T1) and after treatment (6 months later) (T2). The primary aim was to assess pre and post treatment changes in the SPAD in each group, and compare between the two study groups. The secondary aim was to evaluate the sagittal skeletal measurements such as the SNA, SNB, ANB, Wits appraisal, as well as vertical skeletal measurements represented by the Frankfurt-mandibular plane angle (FMA) measured pre- and post-treatment. The independent samples t-test was used to compare the two study groups, and the mean difference and 95% confidence intervals (CI) were computed. The paired samples t-test was used to compare various parameters between T1 and T2 within each group. The cutoff for significance was p-value < 0.05. Data were analyzed using IBM SPSS for Windows (Version 26.0). Results By Comparing changes in airway measurements within each group, it was found that NPAA, OPAA, and LPAA increased significantly after treatment within each group of MB and TB. TB group showed significantly higher mean difference (T2-T1) in both NPAA and OPAA than MB group with 28.39 (± 56.75) and 40.46 (± 52.16) respectively. The increase in LPAA values was not statistically significant at (T2-T1) between both groups. Regarding skeletal changes, there was a significant increase in the SNB values between T1 and T2 within each group with 2.82 (± 3.32) for MB group and 3.79 (± 3.06) for TB group Moreover, there was a significant decrease in the ANB values between T1 and T2 within each group by 2.42 (± 2.70) for MB group and 3.06 (± 1.14) for TB group. Similarly, there was a significant decrease in the ANB values between T1 and T2 within each group by -2.13 (± 0.62) for MB group and − 2.46 (± 0.72) for TB group. No significant differences were found between both groups in SNA, SNB, ANB and Wits appraisal at p = 0.06, p = 0.45, p = 0.43 and p = 0.22 respectively. FMA did not show significant difference between T1 and T2 within each group, nor showed a significant mean difference between both groups at T2-T1. Conclusions TB was more effective than MB in improving the upper (NPAA) and middle (OPAA) airways, while no difference was found regarding the lower airway (LPAA). Both TB and MB reduced the severity of developing skeletal class II due to mandibular retrognathism by forward posturing of the mandible. Thus, patients with airway problems would benefit more from TB than MB.